Penyuluhan Isolasi Mandiri Untuk Mengurangi Penyebaran Covid-19 Pada Pedagang Pasar Desa Pelas Kras Kediri - Nur Azizah Mufarikha; M. Faiz Amiruddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
In 2020, humans were shaken by the corona virus which caused panic everywhere. Hundreds of thousands of people suffered from the virus and thousands more died. Corona virus is a virus that originates from animals and is transmitted through humans. Therefore, the government gives an appeal to the community in overcoming this outbreak, one of which is breaking the Covid-19 chain by means of self-isolation. But there are still many people who do not obey it. Health education activities are currently considered very important, especially in the market environment. Therefore, the program "Self-isolation counseling to reduce the spread of the Covid-19 virus to traders at the Pahing market, Pelas Village, Kras District, Kediri Regency". The purpose of this program activity is to realize the awareness of traders at Pelas market about the importance of maintaining health and preventing the sick from meeting healthy people so that transmission does not occur. The method used by researchers uses interview guidelines and approaches to traders. The targets in this outreach program are traders who experience symptoms of COVID-19. This self-isolation counseling program for traders is considered